Gender and Finance in Sub-Saharan Africa : Are Women Disadvantaged? - Aterido, Reyes; Beck, Thorsten; Iacovone, Leonardo (2012)
This paper assesses whether there is a gender gap in the use of financial services by businesses and individuals in Sub-Saharan Africa. The authors do not find evidence of gender discrimination or lower inherent demand for financial services by enterprises with female ownership participation or by female individuals when key characteristics of the enterprises or individuals are taken into account. In the case of enterprises, they explain this finding with selection bias -- females are less likely to run sole proprietorships than men, and firms with female ownership participation are smaller, but more likely to innovate. In the case of individuals, the lower use of formal financial services by women can be explained by gender gaps in other dimensions related to the use of financial services, such as their lower level of income and education, and by their household and employment status.